Erring Modernization : The Dilemma Of Developing Societies. - Alatas, Syed Hussein (1975)
The old and the vanquished does not immediately descend into the grave. The resistance and' longevity of that which is at the point of vanishing are based on the instinct of 'self-preservation inherent to all that exists.